Hahnemann's legacy—the Q (LM) potencies - Barthel, P. (British Homeopathic Journal, 1991)
The methods of pharmaceutical preparation evolved by Hahnemann between 1801 and 1842 are clearly defined and reproducible. The Q (50th millesimal) potencies offer the shortest, most reliable and ‘most harmless way’ to ‘rapid, gentle and permanent’ restoration to health. An unbiased look at the existing source documents enables us now—150 years later, and after innumerable misunderstandings—to produce and prescribe these highly effective potencies as originally intended. The empirical rule demands: ‘Follow it, but follow it exactly.’
Keywords: Hahnemann; Q potencies; LM potencies; 50th millesimal potencies; Drug manufacture; Prescribing; German Homœopathic Pharmacopoeia